Child Night Blindness and Bitot’s Spots Are Public Health Problems in Lay Armachiho District, Central Gondar Zone, Northwest Ethiopia, 2019: A Community-Based Cross-Sectional Study - Ajebew Bantihun; Kedir Abdela Gonete; Azeb Atnafu Getie; Asmamaw Atnafu (International Journal of Pediatrics)
Background. Night blindness (XN) is a condition in which a person cannot see in dim light and is the earliest clinical manifestation of vitamin A deficiency. Globally, vitamin A deficiency is a public health problem in 122 countries, of which 45 countries have moderate to severe child night blindness. Therefore, this study is aimed at assessing the prevalence and associated factors of night blindness and Bitot’s spot among children aged 24-59 months. Methods. A community-based cross-sectional study was employed from February to March 2019 among children aged 24-59 months in the Lay Armachiho District, Amhara region. A structured and pretested questionnaire was used for data collection. Descriptive summary statistics were used to describe the study population. Bivariate and multivariable logistic regression models were used to identify associated factors. Results. Out of 1007 children, 1.9% and 2.2% had night blindness and Bitot’s spot, respectively. Illiterate mothers (AOR=2.94; 95%CI=1.12,6.72), age of 48 to 59 months (AOR=9.81; 95%CI=1.24,77.36), ≥4 family sizes (AOR=4.52; 95%CI=1.02,19.90), had diarrhea (AOR=5.00; 95%CI=1.73,14.54), and had a respiratory tract infection (AOR=3.14; 95%CI=1.02,9.70) were significantly associated with night blindness. Age of 48-59 months (AOR=4.23; 95%CI=1.13,14.86) and mothers who did not wash their hands after using the toilet (AOR=3.02; 95%CI=1.01,9.13) were predictor variables for Bitot’s spots. Conclusion. The prevalence of night blindness and Bitot’s spots was high. Child’s age, mother’s educational status, family size, diarrhea in the last 2 weeks, and respiratory tract infection in the last 2 weeks were predictive variables for night blindness. Besides, handwashing practice after using the toilet and child’s age were significantly associated with Bitot’s spot among children. Therefore, both night blindness and Bitot’s spots are a public health problem and call for the attention of health professionals in primary health care facilities.